ChemInform Abstract: Synthesis and Characterization of a Novel Quaternary Chalcogenide KBiCu2S3. Issue 15 (15th April 2014) - Zhang, Ganghua; Zhang, Bowen; Chen, Haijie; Zhang, Xian; Zheng, Chong; Lin, Jianhua; Huang, Fuqiang
Abstract KBiCu2S3 is prepared via a facile hydrothermal approach comprising aqueous solutions of KOH, Cu(OAc)2, Bi(NO3)3, and sulfur (autoclave, 240 °C 2—7 d).